2021
DOI: 10.1016/j.jaci.2020.10.044
|View full text |Cite
|
Sign up to set email alerts
|

Association of frequent moisturizer use in early infancy with the development of food allergy

Abstract: Background: Food allergy is thought to develop through transcutaneous sensitization, especially in the presence of skin barrier impairment and inflammation. Regular moisturizer application to infant skin could potentially promote transcutaneous sensitization and the development of food allergy. Objectives: We tested this hypothesis in the Enquiring About Tolerance (EAT) study population. Methods: The EAT study was a population-based randomized clinical trial conducted from January 15, 2008, to August 31, 2015,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
63
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(68 citation statements)
references
References 33 publications
2
63
2
1
Order By: Relevance
“…We stated the concerns about the use of olive oil and other vegetable oils in our article 4 and their potential to impede the development of the lamellar lipid structures. As Leung et al state, 1 this potentially facilitates allergen penetration.…”
Section: To the Editormentioning
confidence: 95%
See 1 more Smart Citation
“…We stated the concerns about the use of olive oil and other vegetable oils in our article 4 and their potential to impede the development of the lamellar lipid structures. As Leung et al state, 1 this potentially facilitates allergen penetration.…”
Section: To the Editormentioning
confidence: 95%
“…In reference to Leung et al, 1 among infants with eczema in the Enquiring about Tolerance (EAT) study at 3 months of age, there was indeed an association between the frequency with which these infants were moisturized and the severity of their eczema, as we reported in our article. 4 However, in our logistic models we adjusted for eczema severity (as well as for filaggrin mutation status and transepidermal water loss), and the association between moisturization frequency and subsequent food allergy development remained robust. Inaccurate recall was not likely in the EAT cohort because of the study's prospective nature and close follow-up of the participating families through monthly questionnaires, in addition to the face-to-face visits.…”
Section: To the Editormentioning
confidence: 97%
“…However, as Perkin et al found, moisturizing infants' skin can also promote food allergy. The authors explained that moisturizers can make it easier for food allergens to break the skin barrier or damage the skin barrier and enable the penetration of the food allergen [50]. Beyond proper skin care, a second important aspect of dual-allergen exposure theory is the importance of introducing foods orally at the right time to stimulate tolerance.…”
Section: Cutaneous Exposure-dual-allergen Exposure Hypothesismentioning
confidence: 99%
“…In the March 2021 issue of the Journal of Allergy and Clinical Immunology, investigators reported an association of frequent moisturizer use in early infancy with the development of FA. 1 We want to highlight several important considerations regarding this study.…”
Section: To the Editormentioning
confidence: 99%